On the membrane paradigm and spontaneous breaking of horizon BMS symmetries - Eling, C; Oz, Y (Springer Verlag, 2016)
We consider a BMS-type symmetry action on isolated horizons in asymptotically at spacetimes. From the viewpoint of the non-relativistic eld theory on a horizon membrane, supertranslations shift the eld theory spatial momentum. The latter is related by a Ward identity to the parti- cle number symmetry current and is spontaneously broken. The corresponding Goldstone boson shifts the horizon angular momentum and can be detected quantum mechanically. Similarly, area preserving superrotations are spontaneously broken on the horizon membrane and we identify the corresponding gapless modes. In asymptotically AdS spacetimes we study the BMS-type symmetry action on the horizon in a holographic super uid dual. We identify the horizon supertranslation Goldstone boson as the holographic super uid Goldstone mode.